Market access and resource endowment define the soil fertility status of smallholder farming systems of South‐Kivu, DR Congo. (20th December 2020) - Balume Kayani, Isaac; Agumas, Birhanu; Musyoki, Mary; Nziguheba, Generose; Marohn, Carsten; Benz, Martin; Vanlauwe, Bernard; Cadisch, Georg; Rasche, Frank
Abstract: This study verified the inter‐related effect of 'market distance', defined as walking time, 'farm typology', defined as resource endowment, and 'site', defined as geographic location with contrasting agro‐ecologies, as well as farmers' indigenous knowledge on soil fertility variability in smallholder farming systems in two distinct regions (Bushumba, Mushinga) of South‐Kivu, DR Congo. A total of 384 soil samples were selected from representative farmers' fields and analysed for soil pH, soil organic carbon (SOC) content and quality, as well as nutrient contents, using midDRIFTS (mid‐infrared diffuse reflectance Fourier transform spectroscopy) and wet chemistry analyses. MidDRIFTS was also used to calculate SOC stability indexes as SOC quality proxies. 'Market distance' and 'farm typology' were key determinants of soil fertility variability, both with contrasting trends in Bushumba and Mushinga. Decreasing soil fertility with increasing market distance was noted across all farm typologies. 'Farm typology' was related to exchangeable calcium and magnesium, while 'site' resulted in a difference of plant available phosphorus. SOC quality indexes were related to 'site', interacting with 'market distance'. A 'market distance' effect became obvious in the medium wealthy and poor farms of Mushinga, where a lower SOC quality in remote fields plots was noted with increasing market distance. In agreement with farmers' indigenous knowledge, soil fertility levels were higher in deep than shallow soils, which were reflected in higher nutrient stocks in deep soils receiving organic amendments. Our results inferred that soil fertility variability across smallholder farms must consider various inter‐related determinants as basis for site‐specific fertility management interventions.